2017
DOI: 10.1007/s11010-017-2991-3
|View full text |Cite
|
Sign up to set email alerts
|

Carnosine modulates nitric oxide in stimulated murine RAW 264.7 macrophages

Abstract: Excess nitric oxide (NO) production occurs in several pathological states, including neurodegeneration, ischemia, and inflammation, and is generally accompanied by increased oxidative/nitrosative stress. Carnosine (β-alanine-histidine (β-Ala-His)) has been reported to decrease oxidative/nitrosative stress-associated cell damage by reducing the amount of NO produced. In this study, we evaluated the effect of carnosine on NO production by murine RAW 264.7 macrophages stimulated with lipopolysaccharides + interfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
67
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 66 publications
(83 citation statements)
references
References 42 publications
12
67
0
2
Order By: Relevance
“…Furthermore, strong evidence that carnosine protects against pathologies characterized by oxidative stress and/or inflammation such as diabetes [29], depression [30], cerebral ischemia [31] and Alzheimer's disease (AD) [32] has been proved. In previous studies, we showed that 20 mM carnosine is highly effective to positively regulating macrophage and microglial functions [23,33]. In particular, we found that carnosine, in macrophages challenged with LPS + IFN-γ, increases the rate of NO transformation into its stable end-product nitrite, modulates the composition of macrophage sub-populations and decreases the release of pro-inflammatory cytokines into the cell medium.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…Furthermore, strong evidence that carnosine protects against pathologies characterized by oxidative stress and/or inflammation such as diabetes [29], depression [30], cerebral ischemia [31] and Alzheimer's disease (AD) [32] has been proved. In previous studies, we showed that 20 mM carnosine is highly effective to positively regulating macrophage and microglial functions [23,33]. In particular, we found that carnosine, in macrophages challenged with LPS + IFN-γ, increases the rate of NO transformation into its stable end-product nitrite, modulates the composition of macrophage sub-populations and decreases the release of pro-inflammatory cytokines into the cell medium.…”
mentioning
confidence: 75%
“…The specific conditions employed to culture and maintain RAW 264.7 cells are the same previously described in details [33]. On the day of the experiment, cells were harvested, an aliquot of the cell suspension was used for cell counting (performed by using a C-Chip disposable hemocytometer and the trypan blue solution) and it was plated in polystyrene culture flasks or Petri dishes at the appropriate density.…”
Section: Cell Culture and Treatment Protocolmentioning
confidence: 99%
“…Other physiological functions of carnosine include the regulation of sarcoplasmic reticulum Ca 2+ -release channels and sarcoplasmic reticulum Ca 2+ homeostasis in skeletal muscle, activation of its phosphorylase activity to promote glycogen breakdown (Johnson et al 1982), inhibition of the angiotensin converting enzyme, enhancement of nitric oxide availability in endothelial cells, potentiation of cardiac and skeletal muscle contractilities, serving as a neurotransmitter or a neuromodulator, as well as the modulation of excitation-contraction coupling in skeletal muscle and the activity of the sympathetic nerve innervating the muscle (Nagai et al 2019;Berezhnoy et al 2019). Carnosine also plays a role in the inhibition of the growth and migration but induction of apoptosis of tumor cells, including human glioblastoma cells as well as colorectal and ovarian carcinoma cells (Hipkiss and Gaunitz 2014;Hsieh et al 2019;Iovine et al 2016), as well as the suppression of the release of interleukin-6 by lipopolysaccharides plus interferon-γ-activated macrophages (Caruso et al 2017). Most recently, carnosine was reported to influence epigenetic regulation of gene expression in mammalian cells via increased histone acetylation (Oppermann et al 2019).…”
Section: Physiological Functions Of Carnosinementioning
confidence: 99%
“…Previous studies by our group and others have shown that carnosine reduces iNOS-facilitated NO production in cells [43,4950]. In contrast, it is proposed that Ca 2+ pre-treatment caused a decrease in the NO/O 2 −• ratio due to an increase in intracellular O 2 −• (and not a decrease in NO).…”
Section: Resultsmentioning
confidence: 82%
“…It has been clearly demonstrated that carnosine is able to scavenge RNOS [42]. Recently, Caruso et al have reported that carnosine can catalyze the conversion of NO into nitrite, thereby causing a decrease in the apparent intracellular NO concentration [43]. We have also shown that significant amounts of carnosine are taken up by macrophages when it is incorporated in the cell culture medium [44].…”
Section: Resultsmentioning
confidence: 85%